Paul S. Latherow papers - Latherow, Paul S. (Paul Scott), 1918-
Flight logbook, photographs, and photocopies of photographs relating to Latherow's service as a pilot in the Pacific theater during World War II, in Germany during the Berlin blockade and airlift (1948-1949), and in the Korean War (1950-1953).
U.S. Army and Air Force officer and pilot.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Korean War, 1950-1953 -- Aerial operations, American; World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Pacific Ocean; Berlin (Germany) -- History -- Blockade, 1948-1949.; Aviators; Air Force officers; Army officers